Achieving food security and industrial development in Malawi: Are export restrictions the solution?. (August 2018) - Aragie, Emerta; Pauw, Karl; Pernechele, Valentina
Highlights: Evaluates the efficacy of export restrictions to promote food security and industrial growth in developing countries. The use of an economywide framework is an advancement over traditional partial equilibrium approaches. Highlights inconsistency between stated policy goals and outcomes due to behavioral responses, especially in the longer run. Advocates for more liberal export policies to support private sector-led economic transformation in developing countries. Abstract: Restrictions on staple or cash crop exports are frequently imposed in developing countries to promote food security or industrial development. By diverting production to local markets, these policies tend to reduce prices and increase domestic supply of food or intermediate inputs in the short term, to the benefit of consumers or manufacturers, which make them attractive to policymakers. However, in the long term, export restrictions discourage agricultural production, which may ultimately negate the short-term gains. This study assesses the economy-wide effects of Malawi's long-term maize export ban, which was only recently lifted, and a proposed oilseed export levy intended to improve food security and support local processing industries, respectively. We find that maize export bans only benefit the urban non-poor, while poor farmers' incomes and maize consumption levels decline in the longer run. The oilseed export levy also fails to achieve its long run objectives: even when tax revenues are used to further subsidize food processors, their gains in value-addition are outweighed by declining agricultural value-addition. More generally, these results show that while export restrictions may have the desired outcomes in the short run, production responses may render the policies ineffective in the medium to long run. Ultimately, such restrictive policies reinforce a subsistence approach to agriculture, which is inconsistent with the stated economic transformation goals of many Sub-Saharan African countries.